Do topical ozone therapy procedures cause side effects during the treatment of chronic wounds? Our own experience - Pasek, Jarosław; Szajkowski, Sebastian; Travagli, Valter; Cieślar, Grzegorz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2026)
Ozone therapy is an innovative therapeutic method that has been used and applied in many areas of medicine, where it has been valued primarily for its viral, bacterial and fungicidal effects. In the case of ozone therapy treatments, ozone can be administered to the body in various ways. Ozone therapy may take the form of a dry bath in an oxygen-ozone mixture, dressings made of ozone water or oil treated with ozone, and in the form of intra-articular or intravenous (so-called autohemotransfusion) administration of ozonated fluids. Ozone is an allotropic form of oxygen. It is an unstable, non-flammable compound that dissolves well in water. Thanks to its beneficial properties and versatile effects, ozone therapy has been getting more and more popular as a supportive therapy for various diseases and ailments, with therapeutic effectiveness confirmed in clinical trials. In high concentrations, ozone is a gas poisonous to humans. The documented research is more scarce as regards the potential for ozone to cause adverse side effects during treatments, depending on the duration of exposure and the concentration of ozone applied in air or other media, such as water or oil. In the present article, the authors present their own observations aimed at determining possible side effects when performing local ozone therapy treatments with the use of oxygen-ozone gaseous mixture for difficult-to-heal wounds.